LOCATION, LOCATION, LOCATION! AN ANALYSIS OF THE LEGAL GROUNDS FOR REQUIRING ALTERNATIVE ACCOMMODATION TO BE PROVIDED CLOSE TO THE EVICTION SITE - Fick, Sarah (Obiter, 2023)
This article explores the notion of “location” in respect of the State’s housing duty, especially in respect of emergency housing. Throughout, the term “location orders” are used to describe orders in which the State is required to provide emergency housing at or near a specific location. It is important to determine the legal justification for such orders, to ensure legal certainty. To answer this question, this article first sets out the facts of the most recent case in which such an order was made (Commando v Woodstock Hub (Pty) Ltd. Secondly, it considers the legal framework applicable to the question. Thirdly, the paper considers the history of location orders in our Constitutional Court’s jurisprudence and how they came about. Thereafter, it explores the court’s justifications for such orders. It considers under what circumstances courts are likely to grant such orders. This is applied to the Commando decision, to determine whether the decision was in line with the current approach. Final remarks are provided in the conclusion.